2006
DOI: 10.1111/j.0014-3820.2006.tb01079.x
|View full text |Cite
|
Sign up to set email alerts
|

Parasite-Host Specificity: Experimental Studies on the Basis of Parasite Adaptation

Abstract: Abstract. Specificity in parasitic interactions can be defined by host genotypes that are resistant to only a subset of parasite genotypes and parasite genotypes that are infective on a subset of host genotypes. It is not always clear if specificity is determined by the genotypes of the interactors, or if phenotypic plasticity (sometimes called acclimation) plays a larger role. Coevolutionary outcomes critically depend on the pervasiveness of genetic interactions. We studied specificity using the bacterial par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 33 publications
4
41
0
1
Order By: Relevance
“…Previous studies (e.g. [11-13]) have observed such a cost, and indeed it seems likely that in the long term there must be a cost of adaptation [9], although this is not always observed [17,18]. It should be noted that our experimental design does not allow us to demonstrate what evolutionary processes led to the observed differences in infectivity.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies (e.g. [11-13]) have observed such a cost, and indeed it seems likely that in the long term there must be a cost of adaptation [9], although this is not always observed [17,18]. It should be noted that our experimental design does not allow us to demonstrate what evolutionary processes led to the observed differences in infectivity.…”
Section: Discussionmentioning
confidence: 81%
“…Conversely, parasite adaptation was found within five generations in the D. magna-Pasteuria system [27]. This difference is peculiar given that the Pasteuria study started with a single strain, whereas we used a diverse mixture of Caullerya spores, suggesting greater evolutionary potential.…”
Section: Discussionmentioning
confidence: 93%
“…In this system however, although phages were allowed to burst kill and persist in the environment, the persistence phase in harsh conditions was a separate experimental step from the replication in E. coli , potentially eliminating the possibility for alternative strategies to evolve and compete [39]. Examples of increased virulence do also exist, for example, Little et al , [40] demonstrated in the D. magna – P. ramosa system that P. ramosa , a burst killer, increased in virulence upon adaptation to a specific host genotype without transmissive stages being present, even though King et al [41] have demonstrated empirically that long lived stage are formed. This was, however, a serial passage experiment, where the host could not evolve in response and it has been shown empirically in the same system that an optimal level of virulence exists [3].…”
Section: Resultsmentioning
confidence: 99%